Comments on the biology of Sciodrepoides watsoni watsoni (Spence, 1813) with descriptions of larvae and pupa (Coleoptera: Leiodidae: Cholevinae) - Kilian, Aleksandra; Mądra, Anna (Zootaxa, 2015)
The late-instar larva of Sciodrepoides watsoni watsoni is redescribed and the egg, first and second instar and pupa are described for the first time. Immature stages habitus, chaetotaxy, detailed illustrations and details of life cycle are provided. Previous descriptions of larva of S. watsoni are discussed. The structures of larvae of S. watsoni are compared with those of other known larvae of Cholevinae.